Sensitivity analysis of chloride induced deterioration in concrete bridges - Rafiq, Meena Imran; Chryssanthopoulos, Marios K.; Onoufriou, Toula (My University, 2004)
Scientific/semi-empirical models have been developed to estimate and predict the extent of deterioration in concrete structures. Input parameters of these models are fraught with uncertainties. These are attributed to the variation in concrete properties and exposure conditions in time and space, and lack of data regarding these variations. Different models for these input parameters have been proposed that have a varying influence on the pre-dicted performance. A methodology has been developed by the authors that uses infor-mation obtained by structural health monitoring to improve confidence in the predicted performance by reducing uncertainties. This paper analyses the sensitivity of different in-put models on the prior and posterior predicted performance. The results quantify the ef-fects of these uncertainties and highlight the effectiveness of the updating methodology based on structural health monitoring.
Keywords: chloride; concrete bridges